The Teddy Bear Hospital. How to influence the attitude of kindergarten children towards doctors, hospitals and falling ill. - Ruth van Sommeren; Mart Ottenheim (European Teacher Education Network, 2018)
Around the world Teddy Bear Hospitals are organized aiming to reduce children's fear of hospitals, doctors and illnesses. In the Netherlands, this project is organized in several cities by the International Federation of Medical Students' Association (IFMSA). The short-term effects of the Teddy Bear Hospital (TBH) held at the Leiden University Medical Centre (LUMC) on 543 kindergarten children were studied. During the project the participating schools were supplied with educational materials around the theme "hospital", to prepare for the visit. The package included picture books, a stuffed animal, songs, colouring activities and explanatory posters. Shortly after the school lessons the children brought their own teddy bear or other stuffed animal to the Teddy Bear Hospital to be "treated". During the hospital visit the children were helped by medical students to use imaginative play to cure their teddy bears. On three different occasions the children's attitude toward doctors, hospitals and illnesses was measured using a seven point Likert scale in the form of emoticons instead of numbers. In the first test the baseline was established, the second test after the hospital themed activities at their own schools and the third test was taken after the Teddy Bear Hospital in the Leiden University Medical Centre. Kindergarten children acquired a more positive attitude toward doctors, falling ill and hospitals. The shift in attitude toward falling ill can be coupled to the pre-visit lessons while the shift in attitude towards doctors and hospital can be attributed to the actual visit to the Teddy Bear Hospital suggesting a positive role for real life learning in schools. A shift in attitude might in the future life of the child lead to a positive attitude to the profession of doctor and perhaps, beta studies in general.